OC-079 Role of metal vs plastic stents for endoscopic ultrasound guided drainage of peri-pancreatic fluid collections: a systematic review and meta-analysis. (17th June 2017) - Ramesh, J; Saunders, R; Cicconi, S; Sutton, R; Neoptolemos, JP; Halloran, C
Abstract : Introduction: The use of fully covered metal stents (FCSEMS) and specifically designed lumen apposing metal stents (LAMS) for transmural drainage of peri-pancreatic fluid collections has become widespread. A systematic review published in 2015 1 did not support the routine use of metal stents for drainage of pancreatic fluid collections. However, recent studies have shown conflicting data; therefore a systematic review and meta-analysis was performed. Method: We conducted a Pubmed search for English language original comparative studies between plastic and metal stents from January 2014 to January 2017. The random effects model was used to calculate pooled risk ratios (RR) with 95% confidence intervals (CI). Outcomes analysed were clinical success, defined as near complete or complete resolution of the pseudocyst on imaging, adverse events and requirement of further intervention. Results: The search identified 183 studies, 6 studies 2-7 with 592 (284 metal, 308 plastic) patients met inclusion criteria and were included in the meta-analysis. Clinical success was achieved in 96.1% vs 87.5%, in the metal and plastic groups respectively, RR 1.08 [95% CI 1.01–1.15], I 2 =38.1%. The rate of adverse events was 10.7% for metal stents vs 26.6% for plastic, RR 0.43 [95% CI 0.21–0.88], I 2 =53.5%. Further intervention was required in 18.2% of patients in the metal stent group vs 27.3% RR 0.61 [95% CI 0.22–1.71], I 2 = 73.6%. Conclusion: Metal stent usage for drainage of peripancreatic fluid collections improves clinical outcomes and reduces adverse events. References: . Bang J, et al. Dig Endosc2015;27(4):486–98. . Lee B, et al. Endoscopy2014;46(12):1078–84. . Mukai S, et al. Endoscopy2015;47(1):47–55. . Bang J, et al. Dig Endosc2017;29(1):83–90. . Bapaye A, et al. Dig Endosc2017;29(1):104–110. . Ang T, et al. Endosc Ultrasound2016;(5): 320–7. . Sharaiha R, et al. Gastrointest Endosc2015;82(5):822–7. Disclosure of Interest: None Declared